Predictive value of dobutamine echocardiography and positron emission tomography in identifying hibernating myocardium in patients with postischaemic heart failure. Issue 3 (1st March 1998) - Pagano, D; Bonser, R S; Townend, J N; Ordoubadi, F; Lorenzoni, R; Camici, P G
Abstract : Objective: To compare the predictive value of dobutamine echocardiography (DE) and positron emission tomography (PET) in identifying reversible chronic left ventricular (LV) dysfunction (hibernating myocardium) in patients with coronary artery disease (CAD) and overt heart failure. Patients: 30 patients (four women) with CAD and heart failure undergoing coronary artery bypass grafting (CABG). Methods: Myocardial viability was assessed with DE (5 and 10 μg/kg/min) and PET with [ 18 F] 2-fluoro-2-deoxy-D-glucose (FDG) under hyperinsulinaemic euglycaemic clamp. Regional (echo) and global LV function (MUGA) were assessed at baseline and six months after CABG. Results: 192 of the 336 (57%) dysfunctional LV segments improved function following CABG (hibernating) and the LV ejection fraction (EF) increased from 23(7) to 32(9)% (p < 0.0001) (in 17 patients > 5%). DE and PET had similar positive predictive values (68% and 66%) in the identification of hibernating myocardium, but DE had a significantly lower negative predictive value than PET (54% v 96%; p < 0.0001). A significant linear correlation was found between the number of PET viable segments and the changes in EF following CABG ( r = 0.65; p = 0.0001). Stepwise logistic regression identified the number of PET viable segments as an independent predictor of improvement in EF > 5%, whereas the number of DE viable segments, the baseline LVEF, and wall motion were not. Conclusions: DE has a higher false negative rate than PET in identifying recoverable LV dysfunction in patients with severe postischaemic heart failure. The amount of PET viable myocardium correlates with the functional outcome following CABG.